دور الإدارة المحلية وتطوير الكفاءات في التنمية المستدلمة على المستوى المحلي - يونس قرواط (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2018)
ملخص** تسعى هذه الدراسة إلى التعرف على مدى قدرة السلطات المحلية ودورها في التنمية المحلية في ظل التنمية المستدامة، وتسليط الضوء على واقع ممارسات الإدارة المحلية، وتطوير الكفاءات، والتحديات التي تواجهها، فضلاً عن فحص العلاقة بين أدوارها ومساهمتها في تحقيق التنمية المحلية المستدامة بأبعادها المختلفة. كما تهدف الدراسة إلى قياس مساهمة المشاريع التنموية على مستوى الإدارة المحلية في تحقيق التنمية المحلية المستدامة، والخروج بنتائج تساعد في تكوين فكرة واضحة حول كيفية الاستفادة من نظام الإدارة المحلية وتطوير الموارد البشرية بما يضمن تحقيق التنمية المستدامة. علاوة على ذلك، تسهم الدراسة في تقديم منتج علمي يثري المكتبة الجامعية من جهة، وتزويد الجهات المختصة بدراسة ميدانية على عينة من البلديات في إحدى ولايات الوسط لتشخيص واقعها من جهة أخرى. ولتحقيق أهداف الدراسة، تم الاعتماد على المنهج الوصفي من خلال أساليب تتوافق مع هذا البحث؛ حيث استُخدمت الاستمارة كأداة أساسية إلى جانب المقابلة والملاحظة في ميدان الدراسة، بالإضافة إلى المنهج السببي المقارن المعني بدراسة تأثير المتغيرات المستقلة على المتغيرات التابعة. كما تم استخدام المنهج الاستقرائي بالاعتماد على دراسة حالة لاختبار مدى مساهمة الإدارة المحلية وتطوير الكفاءات في تحقيق التنمية المستدامة عبر المشاريع التنموية المحلية. تُعد الإدارة المحلية -بأجهزتها الثلاثة (السلطة التقريرية، السلطة التنفيذية، السلطة الرقابية) ومستوياتها (الولاية، البلدية) ذات الصلاحيات المتعددة- عاملاً أساسياً في تحقيق التنمية المحلية المستدامة، نتيجة للوظائف التي تؤديها سواء على الصعيد التنموي أو السياسي، من خلال تلبية الاحتياجات المباشرة للسكان، والتخطيط المستقبلي للتنمية، وتعزيز ديمقراطية المجتمع المحلي في ممارسته لدوره السياسي. وكل ذلك يوحي بأنه لا يمكن تحقيق تنمية محلية مستدامة دون وجود إدارة محلية قادرة على تحقيق التقدم الاقتصادي والاجتماعي على مستواها، نظراً لكونها الجهاز الأقرب لحياة المواطن وبالتالي قدرتها على التأثير في ظروفه المعيشية ومحيطه البيئي. وتشمل الأدوار المهمة للإدارة المحلية، المستمدة من الصلاحيات المخولة لهيئاتها في تحقيق التنمية المستدامة: تخفيض العبء عن السلطات المركزية وإتاحة الفرصة لها للتفرغ لقضايا المشاريع الكبرى، مما يبرز دورها في تحقيق التنمية المستدامة على المستوى الوطني؛ إتاحة فرص مشاركة المواطنين داخل الوحدة المحلية في صنع القرارات والسياسات المحلية والتعاون الوثيق في إعداد الخطط وإثرائها ومتابعة التنفيذ والرقابة؛ الحفاظ على الخدمات الأساسية كالصحة العامة والتعليم ورفع جودتهما؛ حماية التربة والتنوع البيولوجي؛ الاستغلال الأمثل للموارد والتهيئة العمرانية والوقاية من الكوارث الطبيعية؛ والمحافظة على الموارد المائية وتسيير النفايات. **الكلمات المفتاحية:** الإدارة المحلية، الجماعات المحلية، تنمية الموارد البشرية، تطوير الكفاءات، التنمية المستدامة، التنمية المحلية المستدامة.Abstract: This study seeks to identify the extent to which local authorities and its role in local development in sustainable development, and highlight the reality of all of local management practices and develop competencies and challenges it faces, stand on the relationship between their role and contribution to the achievement of sustainable local development in its various dimensions, as the study aims to measure the contribution of development projects for local management level in local sustainable development and the results of this study can contribute to a clear idea about how to take advantage of local management system and develop a human racial ensures sustainable development and contribute to providing a scientific product enriches the university library, and provide custodians with field study on a sample of central states to diagnose their reality. In order to reach the objectives of the study was based on descriptive approach through certain methods that are compatible with this search; use the form as a primary tool alongside the interview and observation. in the field of study, in addition to the method of comparative study of the causal effect of the independent variables on dependent variables. as the use of inductive approach depending on case study and try to test the extent of local management and competency development to achieve sustainable development through local development projects. The local management is with the three organs (declarative authority, executive authority, regulatory authority) and levels (State, municipal) with multiple powers, a key factor in the achievement of sustainable local development, as a result of the functions both in developmental side or from the political side through the provision of immediate needs of the population, and future planning for development, The increase on the democratization of the local community in the exercise of his political role, all this suggests that the achievement of sustainable local development can't be possible without the presence of local management meet to attempt to achieve economic and social progress on the level of being the closest to the citizen's life, and thus their ability to influence the status of living environmental surroundings, and can be the inclusion of some important roles of local management through the powers of their governing bodies in achieving sustainable development, such as reducing the burden on the central authorities and give them the opportunity to devote to issues of major projects which highlighted its role in achieving sustainable development at the national level; and to provide opportunities for participation of citizens in the local unit, making decisions and domestic policies and close cooperation in the preparation of plans, enrich and follow up on implementation and oversight process, in addition to maintaining public services such as health, education, and improving the quality, and the protection of soil biodiversity, the optimal exploitation of resources, and prevention of natural disasters, as well as the conservation of water resources, and the management of wastes. Keywords: local management, local groups, human resources development, competency development, sustainable development, sustainable local development.
دراسة عينة من المشاريع التنموية المحلية في الجزائر
Keywords: الإدارة المحلية; الجماعات المحلية; تنمية الموارد البشرية; تطوير الكفاءات; التنمية المستدامة; التنمية المحلية المستدامة